2020
DOI: 10.1186/s12902-020-0500-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous fertility and variable spectrum of reproductive phenotype in a family with adult-onset X-linked adrenal insufficiency harboring a novel DAX-1/NR0B1 mutation

Abstract: Background: Adrenal hypoplasia congenita (AHC) is an X-linked disorder that affects the adrenal cortex and hypothalamus-pituitary-gonadal axis (HPG), leading to primary adrenocortical insufficiency (PAI) and hypogonadotropic hypogonadism. AHC is caused by a mutation in the DAX-1 gene (NR0B1). More commonly, this disease is characterized by early-onset PAI, with symptoms in the first months of life. However, a less severe phenotype termed late-onset AHC has been described, as PAI signs and symptoms may begin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
2
9
1
Order By: Relevance
“…However, hormonal levels, BTV, age at diagnosis, and gonadotropin treatment response showed no correlations with the molecular variant. This confirms the absence of any clear genotype–phenotype relation in X-AHC patients and the heterogeneity of the pathology reported elsewhere ( 4 , 10 , 12 , 26 , 27 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, hormonal levels, BTV, age at diagnosis, and gonadotropin treatment response showed no correlations with the molecular variant. This confirms the absence of any clear genotype–phenotype relation in X-AHC patients and the heterogeneity of the pathology reported elsewhere ( 4 , 10 , 12 , 26 , 27 ).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, reduced BTV and low or low-normal inhibin B values for age suggest spermatogenesis failure which can be integrated in the hypogonadotropic hypogonadism profile and in the primary gonadal defect reported in X-AHC patients ( 5 , 9 , 10 , 13 ). As observed here, some authors reported testicular volume ranging from 3 to 6 ml bilaterally in most X-AHC cases ( 6 , 9 , 11 , 25 , 26 , 31 , 32 ). However, testicular volume may be normal in mild forms of X-AHC ( 10 ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Initiation of pubertal development cannot be achieved through the use of pulsatile gonadoliberin (GnRH) owing to the pituitary's unresponsiveness to GnRH caused by genetic mutation. Thus, puberty and virilization are achieved either by the injection of human chorionic gonadotropin (hCG), which stimulates testosterone production, or by initiating testosterone replacement therapy, which is often more patient-friendly and less costly [61,62].…”
Section: Gene Mutations Of Dax-1 and Sf-1 As A Cause Of Adrenal Hypop...mentioning
confidence: 99%
“…There are also mutations that interfere with the differentiation of the male reproductive system including cytochrome b5 type A ( CYB5A ) which selectively disrupts 17,20-lyase activity leading to disordered sexual development ( 69 ) and deletions on chromosome 21 that also cause defects in male sexual development ( 70 ). Mutations on the X chromosome are also linked with male infertility including: anosmin 1 ( ANOS1 ), a gene linked to Kallmann syndrome ( 71 ), testis expressed 11 ( TEX11 ), linked to meiotic arrest ( 72 ) and nuclear receptor subfamily 0 group B member 1 (NR0B1) associated with adrenal hyperplasia and hypogonadotropic hypogonadism ( 73 ). Mutations in the X-linked androgen receptor gene are also known to induce infertility in around 2% of male patients ( 74 ).…”
Section: Genetic Causes Of Male Infertilitymentioning
confidence: 99%